Pump-probe spectroscopy and velocimetry of cold atoms in a slow beam - Di Domenico, Gianni; Mileti, Gaetano; Thomann, Pierre (My University, 2001)
In this paper we report on the first purely "pump-probe" nonlinear laser spectroscopy results in a slow atomic beam. We have observed Raman, Rayleigh, and recoil-induced resonances (RIR) in a continuous beam of slow and cold cesium atoms extracted from a two-dimensional (2D) magneto-optical-trap (MOT) with the moving molasses technique. The RIR enabled us to measure the velocity distribution. therefore the average speed (0.6-4 m/s) and temperature (50-500 muK) of the atomic beam. Compared to time of flight, this technique has the advantage of being local, more sensitive in the low-velocity regime (v
Keywords: DIMENSIONAL OPTICAL MOLASSES; RECOIL-INDUCED RESONANCES; POLARIZED; COOLING BEAMS; CESIUM ATOMS; NONLINEAR SPECTROSCOPY; LASER; TRANSMISSION; TRAP